2005
DOI: 10.1021/mp050014h
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Mannose-Functionalized Dendrimers with Pea (Pisum sativum) Lectin

Abstract: Lectins are invaluable tools for chemical biology because they recognize carbohydrate arrays. Multivalent carbohydrate binding by lectins is important for processes such as bacterial and viral adhesion and cancer metastasis. A better understanding of mammalian lectin binding to carbohydrate arrays is critical for controlling these and other cellular recognition processes. Plant lectins are excellent model systems for the study of multivalent protein-carbohydrate interactions because of their robustness and rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
32
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(34 citation statements)
references
References 29 publications
(61 reference statements)
1
32
0
1
Order By: Relevance
“…Results previously reported by Roy et al and Cloninger et al [21][22][23][24] with glycodendrimer-lectin binding interactions strongly suggest that the structural features of these glycodendrimers offer unprecedented opportunities for the design of potent ligands for carbohydrate receptors and as models for the study of those interactions.…”
Section: Introductionmentioning
confidence: 80%
“…Results previously reported by Roy et al and Cloninger et al [21][22][23][24] with glycodendrimer-lectin binding interactions strongly suggest that the structural features of these glycodendrimers offer unprecedented opportunities for the design of potent ligands for carbohydrate receptors and as models for the study of those interactions.…”
Section: Introductionmentioning
confidence: 80%
“…30 It was observed that recognition of the primary sugar by its complementary lectin was enhanced in the presence of the second sugar. Thus, the (aMan) 7 (bLact) 14 heteroglycocluster was more efficient at cross-linking Con A than the (aMan) 7 homogeneous derivative. Similarly, (aMan) 14 (bLac) 7 proved a better PNA cross-linking ligand than (bLac) 7 .…”
Section: (B) Heteroglycoclustersmentioning
confidence: 94%
“…Thus, the (aMan) 7 (bLact) 14 heteroglycocluster was more efficient at cross-linking Con A than the (aMan) 7 homogeneous derivative. Similarly, (aMan) 14 (bLac) 7 proved a better PNA cross-linking ligand than (bLac) 7 . The turbidity experiments evidenced that the supplementary binding enhancement due to the secondary glycotope is sugar-specific, since the formation of the three-dimensional lattices was affected by the presence of a high concentration of the corresponding monovalent sugar in the solution.…”
Section: (B) Heteroglycoclustersmentioning
confidence: 94%
See 1 more Smart Citation
“…Start-burst PAMAM dendrimers are a class of synthetic polymers widely used to deliver bioactive molecules into biological systems. [20] A merit of PAMAM dendrimers is that they can be cleared through kidney [21] which is important for hydrogels used in biofabrication. Due to their water solubility, non-immunogenicity, uniform structures, and ample active functional groups for chemical modifications, they have been extensively used for cancer targeting, [22,23] drug delivery, [24,25] gene delivery, [26,27] and imaging.…”
Section: Introductionmentioning
confidence: 99%